Electrochemical Activity Studies of Glucose Oxidase (GOx)‐Based and Pyranose Oxidase (POx)‐Based Electrodes in Mesoporous Carbon: Toward Biosensor and Biofuel Cell Applications. Issue 10 (11th September 2014) - Kwon, Ki Young; Kim, Jae Hyun; Youn, Jongkyu; Jeon, Chulmin; Lee, Jinwoo; Hyeon, Taeghwan; Park, Hyun Gyu; Chang, Ho Nam; Kwon, Yongchai; Ha, Su; Jung, Hee‐Tae; Kim, Jungbae
Abstract A simple study using a fixed amount of mesoporous carbon (MSU‐F‐C) was performed for the comparison of pyranose oxidase (POx) and glucose oxidase (GOx) in their electrochemical performance under biosensor and biofuel cell operating modes. Even though the ratio of POx to GOx in the glucose oxidation activity per unit weight of MSU‐F‐C was 0.35, the ratios of POx to GOx in sensitivity and power density were reversed to be 6.2 and 1.4, respectively. POx with broad substrate specificity and an option of large scale production using recombinant E. coli has a great potential for various electrochemical applications, including biofuel cells.